An Evaluation of the Effect of DC’s Voucher Program on Public School Achievement and Racial Integration After One Year - Greene, Jay P.; Winters, Marcus A. (Catholic Education: A Journal of Inquiry and Practice, 2007)
This study evaluates the initial effect of Washing, DC’s Opportunity Scholarship Program (OSP) on the academic performance of public schools and its effects on the opportunities that District students have to attend integrated schools. The OSP is a federally sponsored school voucher program that provides vouchers worth up to $7,500 for an estimated 1,800 to 2,000 students in the District of Columbia. The authors measure whether a public school’s test-score gains are related to its distance to the nearest voucher-accepting private school or the number of voucher schools within a one-mile radius of a public school. The evaluation finds that the OSP has had no academic effect, positive or negative, on the District’s public schools after its first year. The study also compares rates of racial integration in DC’s public schools and private schools participating in the voucher program. This is part of the first-year evaluation of the OSP. The authors plan to continue evaluating the OSP using a variety of approaches.